The Role of Logistics in Industrial Side Stream Utilisation - Case: Aqueous Paint Sludge - Tero Leppänen; Pasi Rönkkö; Harri Haapasalo; Pekka Tervonen (International School for Social and Business Studies, 2022)
Purpose: In this article, the utilisation of a case side stream, aqueous paint sludge is studied in accordance with the principles of the circular economy. The study's main objective is to find new potential utilisation possibilities for aqueous paint sludge generated in the region and take a closer look at the role of logistics in the industrial side stream utilisation-based business cases and value chains. Study design/methodology/approach: In this article, the utilisation of aqueous paint sludge is studied via a descriptive case study in the context of Northern Ostrobothnia, Finland. The current state of the paint sludge problem was analysed by interviewing five company representatives. In addition, a workshop was organised, and before the workshop, a questionnaire was sent to all invited. Findings: As a result, the most feasible solutions for aqueous paint sludge utilisation were identified and evaluated from economic, technical, and environmental points of view in the context of this study. In all the proposed solutions, one general challenge was the logistics for narrow material flows from decentralised sources in a relatively large geographical area. Originality/value: Prior case studies of paint sludge utilisation as a raw material have been conducted, but the logistics have not played a significant role in the studies. Logistics has been an important part of the circular economy in the literature. This study reaffirms this notion and finds logistics to have an important and decisive role in industrial side stream utilisation-based business cases and value chains.